Thermosensitive in situ Otic Gel: A Modern Approach for the Topical Management of Otitis Media with Its Formulation Aspects - Shahu, Prachi A. (Asian Journal of Pharmaceutics (AJP), 2023)
An increasing number of in situ forming systems for many biomedical applications have been published in the literature in recent years. Otitis media (OM), most common condition which is caused due to the infection of virus and bacteria. Otitis media is classified into two types: acute and chronic. The most often isolated pathogens in OM are Streptococcus pneumoniae, non-typeable Haemophilus influenza, and Moraxella catarrhalis. Otalgia, ear drainage, fever, restlessness, earache, headache, mild deafness, and difficulty sleeping are all symptoms of otitis media. The global impact of Chronic Suppurative OM sickness includes up to 330 million people having issue of draining ears, 60% (up to 200 million) have significant hearing difficulty. Thailand had prevalence rates ranging from 0.9 to 4.7%, whereas India has a high frequency of 7.8%. Ear drop has drawbacks such as a shorter residence time frame in the ear. Semisolid preparation includes drawbacks such as administrative complexity. Both of these issues can be solved by developing a solution that forms an in situ gel after administration. Solvent exchange, UV-irradiation, ionic cross-linkage, pH alteration, and temperature modulation are few examples of the mechanisms. Because it does not involve the use of organic solvents, copolymerization agents, or a locally applied gelation trigger, the thermosensitive technique may be desirable for some applications. The benefits of in situ polymeric delivery methods include ease of administration and minimized frequency of administration, in addition to improved patient compliance and comfort. At body temperature, poloxamer 407 aqueous solutions (more than 18% w/v) can produce in situ gel.